2006
DOI: 10.1007/s10350-005-0275-6
|View full text |Cite
|
Sign up to set email alerts
|

A Stoma Quality of Life Scale

Abstract: The Stoma Quality of Life Scale demonstrates reasonable psychometric properties for measuring quality of life in patients with stomas. Further studies are needed to refine the instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 22 publications
1
65
0
6
Order By: Relevance
“…Stoma creation entails substantial morbidity and an obvious decrease in quality of life, with major psychological repercussions [19]. Nugent et al [20] reported that up to 80% of patients with a stoma experience alterations in lifestyle, body image, and behavior as well as problems with sexual life in 46%.…”
Section: Discussionmentioning
confidence: 99%
“…Stoma creation entails substantial morbidity and an obvious decrease in quality of life, with major psychological repercussions [19]. Nugent et al [20] reported that up to 80% of patients with a stoma experience alterations in lifestyle, body image, and behavior as well as problems with sexual life in 46%.…”
Section: Discussionmentioning
confidence: 99%
“…We used the City of Hope Quality of Life for Ostomates (mCOH-QOL-Ostomy) [36] questionnaire rather than other ostomy-specific tools (e.g., Stoma Quality of Life Scale) [37,38] in part because it contains openended questions, allowing participants to respond to questions in their own words. One open-ended item asked patients to discuss the greatest challenge they have faced in living with an ostomy.…”
Section: Introductionmentioning
confidence: 99%
“…scale (SQOLS) [30], Short Questionnaire to assess Healthenhancing physical activity (SQUASH) [31], Hospital Anxiety and Depression Score (HADS) [32], multidimensional fatigue score (MFI-20) [33] and the Self-administered Comorbidity Questionnaire (SCQ) [34] Questionnaires are provided at enrollment (baseline) and 3, 6, 12, 18 and 24 months thereafter, followed by an annual questionnaire for the remainder of their participation or until death. The comprehensive selection of PROM questionnaires which are administered frequently at pre-defined time points enable the use of PROMs as consistent endpoints in research.…”
Section: Longitudinal Assessment Of Promsmentioning
confidence: 99%